Antiangiogenic activity of 2-deoxy-D-glucose. - Jaime R Merchan; Krisztina Kovács; Jaclyn W Railsback; Metin Kurtoglu; Yuqi Jing; Yolanda Piña; Ningguo Gao; Timothy G Murray; Mark A Lehrman; Theodore J Lampidis (PLoS ONE)
Background During tumor angiogenesis, endothelial cells (ECs) are engaged in a number of energy consuming biological processes, such as proliferation, migration, and capillary formation. Since glucose uptake and metabolism are increased to meet this energy need, the effects of the glycolytic inhibitor 2-deoxy-D-glucose (2-DG) on in vitro and in vivo angiogenesis were investigated. Methodology/principal findings In cell culture, 2-DG inhibited EC growth, induced cytotoxicity, blocked migration, and inhibited actively forming but not established endothelial capillaries. Surprisingly, 2-DG was a better inhibitor of these EC properties than two more efficacious glycolytic inhibitors, 2-fluorodeoxy-D-glucose and oxamate. As an alternative to a glycolytic inhibitory mechanism, we considered 2-DG's ability to interfere with endothelial N-linked glycosylation. 2-DG's effects were reversed by mannose, an N-linked glycosylation precursor, and at relevant concentrations 2-DG also inhibited synthesis of the lipid linked oligosaccharide (LLO) N-glycosylation donor in a mannose-reversible manner. Inhibition of LLO synthesis activated the unfolded protein response (UPR), which resulted in induction of GADD153/CHOP and EC apoptosis (TUNEL assay). Thus, 2-DG's effects on ECs appeared primarily due to inhibition of LLOs synthesis, not glycolysis. 2-DG was then evaluated in two mouse models, inhibiting angiogenesis in both the matrigel plug assay and the LH(BETA)T(AG) transgenic retinoblastoma model. Conclusions/significance In conclusion, 2-DG inhibits endothelial cell angiogenesis in vitro and in vivo, at concentrations below those affecting tumor cells directly, most likely by interfering with N-linked glycosylation rather than glycolysis. Our data underscore the importance of glucose metabolism on neovascularization, and demonstrate a novel approach for anti-angiogenic strategies.